To the issue of the concept of national identity - Erokhin, Vladimir Sergeevich (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2024)
Introduction. The article is devoted to the analysis of national identity as a socio-political phenomenon. The problem under study is the conceptual ambiguity of the content of the concept of «national identity», signifi cant discrepancies in its interpretation. Theoretical analysis. The purpose of the work is to analyze the content of this concept and to study its essential features. The use of logical and critical methods in the analysis of the concept of «national identity» allows us to identify its important features and analyze its dual nature. The theoretical signifi cance of the work consists in the conceptual analysis of the scientifi c concept of «national identity». Conclusion. The scientifi c novelty lies in the formation of the author’s interpretation of the concept of «national identity»: it is the result of achieving a stable relationship between a person and a national community, the acquisition of a set of signs that allow a person to realize his belonging to the ideals, norms and principles of the existence of the nation. The image of a collective «we» is being formed, supported by the institution of the state. The political side of national identity objectifi es the properties of the nation as a collective «we». The dual nature of national identity includes a combination of the activity of state institutions and the free, active nature of a man as a citizen. The presented understanding of national identity can be used in the process of formation and practical implementation of the state identity policy.